Efektivitas Penerapan Standar Operasional Terhadap Pelayanan Publik Di Kelurahan Penanae Kota Bima - Muhamad Iptidaiyah; Taufik Irfadat (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
To improve the ability of the kelurahan government, both the ability to take initiatives, initiatives, planning, implementation and supervision, so as to obtain good government performance, then the kelurahan is the working area of the lurah as a district / city regional apparatus under the sub-district which is responsible to the camat. Kelurahan has the task and function of carrying out government authority delegated by the camat and carrying out other government tasks in accordance with applicable laws and regulations. The working relationship between sub-districts and urban villages is hierarchical. The establishment of the kelurahan is intended to improve the ability to implement the kelurahan government in an efficient and successful manner in providing services to the community in accordance with the level of development and progress of development. Based on the results of the researcher's observations that at the Penanae Urban Village office the Population Administration Standard Operating Procedures have been implemented and carried out, but the implementation of the SOP has not been fully effective in KK and Birth Certificate services even though a 15-minute completion time has been set but there are still delays in completion and not in accordance with the SOP in Penanae Village. The delay occurs within 1 day and even more than 1 day. Even though the SOP provision should be 15 minutes in making it.